(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article examines the phraseologies of some English works that are used to convey specific ideas, images and emotions. It also plays an important role in creating atmosphere, characters and plot, making texts more lively and interesting for readers.